A partial lower jaw of a tetrapod from "Romer's Gap". (March 2017) - Chen, Donglei; Alavi, Yasaman; Brazeau, Martin D.; Blom, Henning; Millward, David; Ahlberg, Per E.
ABSTRACT: The first half of the Mississippian or Early Carboniferous (Tournaisian to mid- Viséan), an interval of about 20 million years, has become known as "Romer's Gap" because of its poor tetrapod record. Recent discoveries emphasise the differences between pre-"Gap" Devonian tetrapods, unambiguous stem-group members retaining numerous "fish" characters indicative of an at least partially aquatic lifestyle, and post-"Gap" Carboniferous tetrapods, which are far more diverse and include fully terrestrial representatives of the main crown-group lineages. It seems that "Romer's Gap" coincided with the cladogenetic events leading to the origin of the tetrapod crown group. Here, we describe a partial right lower jaw ramus of a tetrapod from the late Tournaisian or early Viséan of Scotland. The large and robust jaw displays a distinctive character combination, including a significant mesial lamina of the strongly sculptured angular, an open sulcus for the mandibular lateral line, a non-ossified narrow Meckelian exposure, a well-defined dorsal longitudinal denticle ridge on the prearticular, and a mesially open adductor fossa. A phylogenetic analysis places this specimen in a trichotomy with Crassigyrinus and baphetids + higher tetrapods in the upper part of the tetrapod stem group, above Whatcheeria, Pederpes, Ossinodus, Sigournea and Greererpeton . It represents a small but significant step in the gradual closure of "Romer's Gap".